Fitness for life - Corbin, Charles B.; Le Masurier, Guy C.; McConnell, Karen E. (Human Kinetics, 2014)
Fitness for Life, Sixth Edition, is the award-winning text that continues to set the standard for teaching personal fitness (fitness education) at the high school level. It will help students become physically literate individuals who have the knowledge, skills, and confidence to enjoy a lifetime of healthful physical activity. This classic, evidence-based book will guide students in becoming informed consumers on matters related to lifelong physical activity and fitness, taking responsibility for setting individualized goals, and making their own plans for active living. To accomplish this overarching goal, they learn a variety of self-management skills, including self-assessment. The program is based on established educational theory as outlined in the online teacher's guide. Fitness for Life, Sixth Edition, helps students in these ways: Become physically literate individuals as defined by SHAPE America. Meet the national, state, and local grade-level standards and outcomes developed by SHAPE America for physical education and fitness education. Meet college and career readiness standards by learning and using critical thinking, decision making, and problem-solving skills. Meet national physical activity guidelines of the USDHHS, exercise prescription guidelines of ACSM, and health goals of Healthy People 2020. Use the HELP philosophy of promoting health for everyone with an emphasis on lifetime activity and healthy lifestyles designed to meet personal needs. Use the Stairway to Lifetime Fitness concept, created by author Chuck Corbin, to encourage higher-order learning (move from dependence to independence). Use the Physical Activity Pyramid, created by the authors, to help students understand the FITT formula and benefits of the major types of physical activities. Become informed consumers on matters related to lifelong physical activity and fitness and other healthy lifestyles (e.g., good nutrition and stress management). Learn self-management skills that lead to adopting healthy lifestyles. Perform self-assessments, including all tests in the Fitnessgram battery and the Presidential Youth Fitness Program. Take personal responsibility for setting individualized goals and personal program planning. Develop a love for lifetime fitness activities. Benefit from the expertise of internationally renowned authors and educators Charles B. "Chuck" Corbin and Guy C. Le Masurier and contributing author and educator Karen McConnell.